2014
DOI: 10.1111/sltb.12092
|View full text |Cite
|
Sign up to set email alerts
|

A Trait‐Interpersonal Analysis of Suicide Proneness Among Lesbian, Gay, and Bisexual Community Members

Abstract: Suicide remains a concerning issue for lesbian, gay, and bisexual (LGB) persons. The integrated effects of five-factor model personality traits and interpersonal-psychological theory of suicide (IPTS) constructs on suicide proneness in a community sample of 336 LGB adults were examined. Results supported a model inclusive of all five-factor model domains predicting IPTS constructs leading to suicide proneness. Effects of neuroticism and extraversion were both mediated by perceived burdensomeness and thwarted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
(113 reference statements)
6
21
2
Order By: Relevance
“…Thus, all participants in the present study self-identify as, or report attractions/behaviors that are consistent with, the operationalization of sexual minority 2 . Notably, 86 transgender and other gender-identified participants met the sexual minority inclusion criteria; their inclusion is consistent with similar research (e.g., Cramer et al, 2014) and recent theoretical advances suggesting that minority stress processes generalize to gender minorities (Hendricks & Testa, 2012). We restricted our analytic sample to young adults (18–25; M age =20.77, SD =2.05; omitting 292 older adults from the parent study) to focus on this age demographic because approximately one-in-five deaths among persons in this age range are attributable to suicide (Centers for Disease Control and Prevention, 2012).…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, all participants in the present study self-identify as, or report attractions/behaviors that are consistent with, the operationalization of sexual minority 2 . Notably, 86 transgender and other gender-identified participants met the sexual minority inclusion criteria; their inclusion is consistent with similar research (e.g., Cramer et al, 2014) and recent theoretical advances suggesting that minority stress processes generalize to gender minorities (Hendricks & Testa, 2012). We restricted our analytic sample to young adults (18–25; M age =20.77, SD =2.05; omitting 292 older adults from the parent study) to focus on this age demographic because approximately one-in-five deaths among persons in this age range are attributable to suicide (Centers for Disease Control and Prevention, 2012).…”
Section: Methodssupporting
confidence: 78%
“…For instance, utilizing trait-based measurements in clinical settings may improve estimates of individual risk, and inform provider recommendations and practices aimed at preventing suicidality based on individuals’ unique personality profile. For some this might include improving self-regulation strategies (in the case of elevated neuroticism; Roelofs et al, 2008), managing impulsive tendencies (high neuroticism or extraversion, or low conscientiousness, Whiteside & Lynam, 2001), or securing countervailing social support (in the case of higher neuroticism and lower extraversion and/or agreeableness; Cramer et al, 2014) in the face of victimization.…”
Section: Resultsmentioning
confidence: 99%
“…Shame and rejection sensitivity are two constructs that are parallel to the interpersonal theory of suicide's focus on perceived burdensomeness and thwarted belonging (Van Orden et al., ). Although several studies have documented support for perceived burdensomeness and thwarted belonging as risk factors for suicide among sexual minorities (Cramer et al., ; Hill & Pettit, ; Plöderl et al., ; Woodward et al., ), our study extends this work by identifying two additional and nuanced interpersonal factors that are associated with suicide risk. Future work would benefit from testing these relational factors directly with interpersonal theory's factors (e.g., burdensomeness and thwarted belonging).…”
Section: Discussionsupporting
confidence: 57%
“…Although expectations of rejection might serve as protective factors (i.e., being vigilant of future stressors to protect one's self), this prolonged and chronic sense of vigilance can be psychologically draining. Rejection sensitivity also leads to social isolation and may be a key factor in individuals’ perceived belongingness (Downey & Feldman, ), which, according to the interpersonal theory of suicide, is a documented risk factor for suicide among the general population and sexual minorities (Cramer, Stroud, Fraser, & Graham, ; Hill & Pettit, ; Plöderl et al., ). Rejection sensitivity is associated with greater suicidality in clinical samples (i.e., individuals with borderline personality disorder; Soloff, ).…”
Section: Theoretical Models Explaining Suicide Risk Among Sexual Minomentioning
confidence: 99%
“…shown that younger and older males; people of indigenous descent; people living in rural and remote areas; and lesbian, gay, bisexual, transgender and intersex people are at higher risk of suicide [38][39][40][41]. Additionally, psychopathologies such as depression, bipolar disorder and substance abuse are predicted to be present in most cases of suicide [38,40].…”
Section: Studies Of At Risk Populations In Australia and Brazil Havementioning
confidence: 99%